Hepatitis C in Hemodialysis Units: diagnosis and therapeutic approach - Natasha Silva Constancio; Maria Lucia Gomes Ferraz; Carmen Tzanno Branco Martins; Angiolina Campos Kraychete; Paulo Lisboa Bitencourt; Marcelo Mazza do Nascimento (Brazilian Journal of Nephrology, 2019)
Abstract According to data from the last census of the Brazilian Society of Nephrology (SBN), the prevalence of hepatitis C virus (HCV) in Brazilian hemodialysis units (HU) is 3.3%, about three times higher than what is reported for the Brazilian general population. Often, professionals working in HU are faced with clinical situations that require rapid HCV diagnosis in order to avoid horizontal transmission within the units. On the other hand, thanks to the development of new antiviral drugs, the cure of patients with HCV, both in the general population and in patients with chronic kidney disease and the disease eradication, appear to be very feasible objectives to be achieved in the near future . In this scenario, SBN and the Brazilian Society of Hepatology present in this review article a proposal to approach HCV within HUs.